(untitled) (Nigerian Journal of Pharmaceutical Research, 2024)
Background: Formulation of solid self-emulsifying drug delivery system (Solid SEDDS) provides a dual benefit of improved drug stability and enhanced delivery system. Objective: This study was aimed at developing and evaluating a solid self-emulsifying drug delivery system of hydrochlorothiazide. Methods: Solubility of hydrochlorothiazide in some oils was determined and pseudo-ternary system of the most effective oil, water and surfactant system was constructed. Four Liquid SEDDSs were formulated to contain Tween 80/oleic acid or PEG 400/oleic acid (surfactant systems) and castor oil combined in ratio 2:8 or 3:7 based on the pseudo-ternary plot. Each preparation was made by adding the drug to the oil/surfactant system and heating up to 60 0C under continuous stirring followed by cooling to room temperature. Viscosity of each Liquid SEDDS was determined; Solid SEDDS was prepared by mixing the Liquid SEDDS with microcrystalline cellulose in 1:2 proportion and then encapsulated. Drug release profile of the Solid SEDDSs in comparison with a marketed product was studied. Results: Castor oil was found to be the best solvent for hydrochlorothiazide and the viscosity of the Liquid SEDDSs was in the range of 79.41 and 187.32 mPa.s. The in vitro release studies showed 85.46 – 87.17 % drug release from the formulated SEDDSs with ratio 3:7 of surfactant mix being superior; and percentage drug release for each formulation was twice that of the marketed product. Conclusion: The prepared Solid SEDDS of hydrochlorothiazide exhibited improved drug release characteristics, hence superior to the conventional commercial product.